EFEKTIFITAS HIPNOTERAPI TERHADAP PENURUNAN TINGKAT STRESS DALAM MENGERJAKAN SKRIPSI PADA MAHASISWA TINGKAT AKHIR S1 KEPERAWATAN STIKES MUHAMMADIYAH MANADO - Rizkan H. Djafar; Agust A. Laya; Norman Alfiat Talibo (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2021)
Stress is a large imbalance between physical or psychological demands and the ability to respond when there is a failure to meet the demands faced. One method that can be used to reduce stress is hypnotherapy. This study aims to determine the effect of hypnotherapy on the reduction of stress levels in undergraduate students of nursing. The research design used a quasy experiment with two groups pre and post test using a purposive sampling approach which was carried out on the final year students of undergraduate nursing. This research instrument using perceived stress scale. Data analysis using Paired T test. The results of the study on 32 respondents using the Independent T test on the average stress after (posttest) in the Intervention with Control group obtained P value = 0.000 <? (0.05) there is a difference in the average stress after (posttest) in the Intervention group with the group control. Based on this research, hypnotherapy is effective in reducing stress levels and is expected to provide input to other educational and research institutions so that it can overcome stress on students with hypnotherapy.